2007
DOI: 10.1093/aje/kwk114
|View full text |Cite
|
Sign up to set email alerts
|

Association of Ethnicity and Socioeconomic Status with Judgments of Body Size: The Coronary Artery Risk Development in Young Adults (CARDIA) Study

Abstract: The authors assessed the associations of ethnicity and socioeconomic status (SES) with body size judgments in Black and White young adults. Self-perceived and ideal body size judgments were measured using the Stunkard nine-figure scale (higher value = larger body) at the year 7 examination (1992-1993) of the Coronary Artery Risk Development in Young Adults (CARDIA) Study. In sex-specific adjusted multiple regression models, the difference between self-perceived and ideal body size judgments was larger for Whit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
79
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 26 publications
7
79
2
1
Order By: Relevance
“…These finding agree with Lynch et al, (2007) (15) they reported that, thin body is the most preferred body shape in Western countries. Data showed that the first priority of females to loss their weight is to improve confidence and appearance.…”
Section: Bmi Kg/m2supporting
confidence: 93%
“…These finding agree with Lynch et al, (2007) (15) they reported that, thin body is the most preferred body shape in Western countries. Data showed that the first priority of females to loss their weight is to improve confidence and appearance.…”
Section: Bmi Kg/m2supporting
confidence: 93%
“…20 The nine-figure, sex-specific Stunkard rating scale was used as an adjunct to BMI to evaluate self-size awareness. Participants chose silhouettes from underweight, normal weight, overweight, and obese identified as current, ideal, and healthy body image 21 that were compared to the calculated BMI. National guidelines and normative data link the Stunkard figures with BMI; the scale has been tested to have validity and test-retest reliability.…”
Section: Assessment Of Body Sizementioning
confidence: 99%
“…African American and Hispanic adults are more likely than white adults to perceive their current overweight status as closer to an ideal body size, and African Americans in general are more likely to perceive obesity as acceptable, desirable, or sexually attractive. [61][62][63][64][65] Moreover, some of the factors maintaining obesity may have strong cultural determinants related to the role of food. 66 Although not universal, the positive perceptions of excess weight persist despite the known connection between obesity and the very real health threats of diabetes and vascular disease.…”
Section: Social Attributions and Cultural Perceptions Of Increased Wementioning
confidence: 99%